Coffee growth, pest and yield responses to free-air CO2 enrichment - Ghini, Raquel; Torre-Neto, André; Dentzien, Anamaria F. M.; Guerreiro-Filho, Oliveiro; Lost, Regiane [UNESP]; Patrício, Flávia R. A.; Prado, Jeanne S. M.; Thomaziello, Roberto A.; Bettiol, Wagner; Damatta, FÁbio M. (Springer Nature, 2015)
Despite the importance of coffee as a globally traded commodity and increasing concerns about risks associated with climate change, there is virtually no information about the effects of rising atmospheric [CO2] on field-grown coffee trees. This study shows the results of the first 2 years of an innovative experiment. Two commercial coffee cultivars (Catuaí and Obatã) were grown using the first free-air CO2 enrichment (FACE) facility in Latin America (ClimapestFACE). Plants of both cultivars maintained relatively high photosynthetic rates, water-use efficiency, increased growth and yield under elevated [CO2]. Harvestable crop yields increased 14.6 % for Catuaí and 12.0 % for Obatã. Leaf N content was lower in Obatã (5.2 %) grown under elevated [CO2] than under ambient [CO2]; N content was unresponsive to elevated [CO2] in Catuaí. Under elevated [CO2] reduced incidence of leaf miners (Leucoptera coffeella) occurred on both coffee cultivars during periods of high infestation. The percentage of leaves with parasitized and predated mines increased when leaf miner infestation was high, but there was no effect of elevated [CO2] on the incidence of natural enemies. The incidence of rust (Hemileia vastatrix) and Cercospora leaf spot (Cercospora coffeicola) was low during the trial, with maximum values of 5.8 and 1 %, respectively, and there